Emerging Non-OECD Countries: Global Shifts in Power and Geopolitical Regionalization - Sören Scholvin (German Institute of Global and Area Studies (GIGA), 2010)
Various concepts ascribe key roles to emerging non-OECD countries in regional and global politics. This paper highlights how these concepts hint not only at a shift of global power but also at geopolitical regionalization: according to the theory of hegemonic stability, regional powers (a subcategory of emerging non-OECD countries) are key actors in overcoming international anarchy and establishing cooperative and stable relations within their regions. Because of the different impacts of different regional powers, which are categorized in this paper using typologies of hegemony, the logic of international relations varies from one region to another. From a theoretical point of view, this means that international relations theories have to make region-specific adaptations. – – Verschiedene Konzepte schreiben aufstrebenden Nicht-OECD-Staaten Schlüsselrollen in regionaler und globaler Politik zu. Der Autor dieses Aufsatzes hebt hervor, dass solche Konzepte nicht nur auf globale Machtverschiebungen, sondern auch auf geopolitische Regionalisierung hinweisen. Entsprechend der Theorie hegemonialer Stabilität nehmen regionale Führungsmächte (eine Unterkategorie aufstrebender Nicht-OECD-Staaten) eine Schlüsselfunktion in der Überwindung der internationalen Anarchie ein und tragen dazu bei, kooperative und stabile Beziehungen in ihren Regionen herzustellen. Aufgrund der unterschiedlichen Auswirkungen verschiedener regionaler Führungsmächte, die in diesem Aufsatz mittels Typologien von Hegemonie kategorisiert werden, variiert die Logik internationaler Beziehungen von Region zu Region. Aus theoretischer Sicht bedeutet dies, dass Theorien der internationalen Beziehungen regionsspezifisch angepasst werden müssen.
Keywords: 300; regional powers; hegemonic stability; geopolitics; regionalization; Geopolitik; Regionalismus; Schwellenländer; Entwicklungsländer